2018
DOI: 10.22159/ajpcr.2018.v11i1.17532
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heart Failure Causes Osteopathy or Is Osteopathy a Factor in Development of Chronic Heart Failure?

Abstract: Objective: As their proportion rises in the aging population, cardiovascular disease and osteoporosis increasingly become significant health problems of the developed world, leading to reduced lifespan and substantial financial burdens, not the least because of complications and comorbidities associated with each disorder. This study investigates bone mineralization in patients with coronary heart disease (CHD) complicated by Stage I chronic heart failure (CHF). Methods:The study group consisted of 41 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Considering that mental health is an integral part of the general health of people and together with mental well-being it is a high quality of life condition, the presence of mental disorders significantly affects the course of the disease, violating the subjective perception of the disease and reducing the effectiveness of treatment [4][5][6] . The structure of the causes of mortality in Ukraine remains constant: cardiovascular diseases remain in the first place -in 2015 this figure counted up to 404.6 thousand people, which correspond to 68% of total mortality [7][8][9][10] . According to the official statistics, over the past 25 years, the prevalence of cardiovascular diseases among the population of our country has increased by 3 times, and the mortality rate from them has increased by 45%.…”
mentioning
confidence: 99%
“…Considering that mental health is an integral part of the general health of people and together with mental well-being it is a high quality of life condition, the presence of mental disorders significantly affects the course of the disease, violating the subjective perception of the disease and reducing the effectiveness of treatment [4][5][6] . The structure of the causes of mortality in Ukraine remains constant: cardiovascular diseases remain in the first place -in 2015 this figure counted up to 404.6 thousand people, which correspond to 68% of total mortality [7][8][9][10] . According to the official statistics, over the past 25 years, the prevalence of cardiovascular diseases among the population of our country has increased by 3 times, and the mortality rate from them has increased by 45%.…”
mentioning
confidence: 99%
“…Our previous studies showed that structural and functional changes in the bone tissue of the lumbar spine were found in 75.9% of patients with Stage 1 of CHF caused by ischemic heart disease: 64.4% of patients had osteopenic syndrome and 11.5% -osteosclerotic changes. In 75.8% of CHF patients, we have found structural and functional changes in the bone tissue of proximal right femur [13]. Structural and functional changes of bone tissue of the lumbar spine have been found in 49.2% of patients with CHD complicated by Stage II-A CHF, in particular, I stage of osteopenia -in 44.6%, II stage of osteopenia -in 27.7%, III stage of osteopenia -in 10.8%, and osteoporosis -in 16.9% [14].…”
Section: Introductionmentioning
confidence: 83%
“…The first pilot projects on the development 25 . In the structure of non-infectious diseases mortality factors the main factors are diabetes [26][27][28] , cancer, chronic obstructive pulmonary diseases, cardiovascular diseases [29][30][31] . Key risk factors of non-infectious diseases are considered below (see scheme 1).…”
Section: Analysis Of Public Health System Formation In Ukrainementioning
confidence: 99%